A study of the effects of the cathode configuration on the plasma kinetics and neutron emission of plasma-focus discharges in deuterium - Barbaglia, Mario Oscar (2020)
The differences in performance of a 1.9 kJ plasma-focus device PACO assembled with three different cathode configurations are experimentally qualified. In particular, the current sheath kinetics and the neutron yield operating with deuterium gas are systematically studied for the whole range of neutron-producing pressures, and the measurements are analyzed searching for relations between relevant physical magnitudes. The pinching time was found correlated with the dimensionless driver parameter, and this feature was found statistically independent of the cathode. The variation of the inductance jump associated with the radial collapse stage is used to estimate the effective pinch length, (7.3 ± 1.6) mm, and radius, (3.6 ± 2.1 ) mm. The maximum production in a single shot was registered for the smallest cathode radius, 41 mm, whereas the intermediate cathode radius, 45 mm, scored better in average. In all configurations, the neutrons per deuteron pair correlates fairly well with an estimation of the effective equilibrium temperature of the pinch, which suggests a prevalence of thermonuclear neutrons measured perpendicularly to the focus axis.